Lifetime measurements and the high-spin structure of 36Cl. (March 2015) - Aydin, S; Ionescu-Bujor, M; Recchia, F; Gadea, A; Lenzi, S M; Lunardi, S; Ur, C A; Bazzacco, D; Bizzeti, P G; Bizzeti-Sona, A M; Bouhelal, M; de Angelis, G; et al.
Abstract: High-spin states in 36 Cl were populated through the 24 Mg( 14 N, 2p) 36 Cl reaction at E( 14 N)=31 MeV. Lifetimes have been determined for fifteen states by applying the Doppler shift attenuation method. The results indicated the onset of collectivity in the high spin negative parity states. Large basis shell model calculations have been performed to understand the underlying structure of these states.